A személyi jövedelemadó-reform hatása a tb-nyugdíjakra - Zsombor Cseres-Gergely; András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2011)
– The Hungarian Personal Income Tax system is being transformed between 209 and 2013. Tax brackets and the previously existing tax credit is being abolished and this changes the net/gross income ratios in all income categories. This does not only lead to a significant loss in government's income, but also changes redistribution within the society. However, reallocation of net income is not the only change. At present, pension contributions are proportional to gross earnings, while pension benefits are proportional to net earnings. If this situation does not change, a substantial deficit in the pension fund occurs. This paper describes the size of this deficit and its distribution within the society.
Keywords: H23; H55; 330; pension; tax system; taxation; Steuersystem; Einkommensteuer; Altersvorsorge; Ungarn